2019
DOI: 10.1097/jsm.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

Hip and Knee Weakness and Ankle Dorsiflexion Restriction in Individuals Following Lateral Patellar Dislocation: A Case-Control Study

Abstract: Objective: To explore the relationship between ankle dorsiflexion range of motion (ROM) and hip and knee muscle strength between patients with a history of patellar dislocation (PD) to healthy controls. Design: Case-control study. Setting: Orthopaedical specialty outpatient clinic at a tertiary hospital. Participants: 88 individuals were recruited; 44 individuals aged 16 years or older, of both sexes, with a history of at least one episode of atraumatic unilateral or bilateral PD requiring emergency care (14 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Knee extension strength was assessed in all 24 studies; 11 of these also assessed knee flexion strength. 5,6,66,21,27,30,38,41,42,51,54 Hip abduction strength was assessed in three studies, 3,25,54 hip external rotation was assessed in two studies, 3,25 and hip flexion, extension, adduction and internal rotation strength were assessed in one study. 3…”
Section: Lower Limb Muscle Groups Assessedmentioning
confidence: 99%
See 2 more Smart Citations
“…Knee extension strength was assessed in all 24 studies; 11 of these also assessed knee flexion strength. 5,6,66,21,27,30,38,41,42,51,54 Hip abduction strength was assessed in three studies, 3,25,54 hip external rotation was assessed in two studies, 3,25 and hip flexion, extension, adduction and internal rotation strength were assessed in one study. 3…”
Section: Lower Limb Muscle Groups Assessedmentioning
confidence: 99%
“…They found increased pain with slower angular velocities: 6°/second pain pre-surgery = 3.4, post-surgery = 1; 12°/second pain pre-surgery = 2.9, post-surgery = 1.2; and 60°/second pain presurgery = 1.7, post-surgery = 0.6. Four studies 3,21,25,51 did not report any adverse events and it was unclear if adverse events were reported in Liebau et al 23 as the full-text was not translated. In the remaining 17 studies, no reported adverse events related to lower limb strength assessments.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up timepoint was 15 (13)(14)(15)(16)(17)(18)(19) weeks. Two participants had treatment durations of 102 and 116 days, exceeding the three months permissible.…”
Section: Ancillary Analysesmentioning
confidence: 99%
“…Intense leg strengthening and dynamic exercises, such as hopping and changing direction, are rarely used (9,11). As this is mainly a young active patient population that experiences most instability symptoms during multidirectional running and hopping activities (12), and that often fails to restore leg strength symmetry after injury (7,13,14), current rehabilitation programmes may be inadequate. A programme of leg resistance exercises prescribed in accordance with evidence-based guidelines (15), and dynamic exercises that prepare patients for the demands of the activities they wish to resume, could improve outcomes in terms of regaining function and reducing the risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%